Costo beneficio del uso de la facturación electrònica en los contribuyentes de la ciudad de Riobamba, período 2020-2022 - Chacha Chalan, Carolina Lizbeth (2024)
ABSTRACT: ABSTRACT The research seeks to determine the cost-benefit of using electronic invoicing for the taxpayers of Riobamba City, period 2020 - 2022. The research development considered the logical-deductive method under a quantitative, documentary, and field-type approach, with a non-experimental design and a descriptive level. A questionnaire was applied to a sample of taxpayers, considering data collected from the SRI. The electronic billing system provided a higher return in terms of profits compared to traditional and semi-automatic systems. Therefore, this supports the effectiveness and viability of using electronic invoicing in terms of cost-benefit for the taxpayers of Riobamba City. In this sense, the hypothesis was corroborated that the use of electronic billing by taxpayers in the city of Riobamba has a positive impact on administrative efficiency and reduction of operating costs. Keywords: Benefits, costs, taxpayer, electronic billing.